2010
DOI: 10.2353/ajpath.2010.091079
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Acts as a Negative Regulator of β-Catenin Signaling in the Adult Tongue Epithelium

Abstract: Wnt/␤-catenin signaling has been implicated in taste papilla development; however , its role in epithelial maintenance and tumor progression in the adult tongue remains elusive. We show Wnt/␤-catenin pathway activation in reporter mice and by nuclear ␤-catenin staining in the epithelium and taste papilla of adult mouse and human tongues. ␤-Catenin activation in APC min/؉ mice , which carry a mutation in adenomatous poliposis coli (APC), up-regulates Sonic hedgehog (Shh) and Jagged-2 (JAG2) in the tongue epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 44 publications
3
30
0
Order By: Relevance
“…54,59 In addition, sub-cellular localization of markers has been shown to be a better indicator of EMT. 10,14,59,78 A potential possibility is that sub-cellular localization may be an indicator of early EMT whereas total levels may be an indicator of late EMT. Additional work to clarify these potential issues will better delineate the mechanisms that regulate the dynamic EMT program in HNSCC.…”
Section: Resultsmentioning
confidence: 99%
“…54,59 In addition, sub-cellular localization of markers has been shown to be a better indicator of EMT. 10,14,59,78 A potential possibility is that sub-cellular localization may be an indicator of early EMT whereas total levels may be an indicator of late EMT. Additional work to clarify these potential issues will better delineate the mechanisms that regulate the dynamic EMT program in HNSCC.…”
Section: Resultsmentioning
confidence: 99%
“…185 Specifically, HH signalling was found to inhibit Wnt signalling via upregulation of sFRP-1, 185 and to suppress β-catenin transcriptional activity. 186 Furthermore, HH signalling can induce the Notch ligand Jagged2, at least in some models. 187 These findings suggests that HH-pathway inhibitors might, at least in some cases, inhibit Jagged2-mediated Notch signalling, but may also trigger a compensatory increase in Wnt signalling.…”
Section: Crosstalk Between Signalling Pathwaysmentioning
confidence: 99%
“…This crosstalk appears to be mutual and even complex with the involvement of common components but different functional aspects of the GLI transcription factors and tissue specificity. In adult tongue epithelium dominant activation of β-catenin lead to a significant up-regulation of Shh which then diminished β-catenin signaling [180]. Vice versa, IHh is a target of Wnt/β-catenin, and in liver it has been shown that the perivenous area expressing IHh is extended upon activation of β-catenin signaling [164].…”
Section: Hypoxia Hifs and Hedgehog Signaling: Another Liaisonmentioning
confidence: 99%